Model Pengembangan Kemampuan Auditor Dalam Tantangan Era Sosiety 5.0 Di Indonesia - Kurniawati, Selly; Rieswandha Dio Primasatya (Politeknik Ganesha Medan, 2024)
The development of technology-based scientific knowledge has led to digitization in all aspects, giving rise to the era of Society 5.0, which emphasizes the integration of human life with artificial intelligence technology, including business processes. Auditors, as one of the independent professions with a crucial role in maintaining the balance of business processes by ensuring transparency and compliance with agreed-upon procedures, must understand the Society 5.0 era. This understanding can be translated into the form of competency standards, which are the skills and abilities that auditors must possess to fulfill their duties and responsibilities inherent to their profession. The aim of this research is to identify the challenges faced by auditors in the Society 5.0 era and how to adapt the competency standards that need to be met. The research method used is qualitative with a scoping review approach and content analysis techniques in descriptive data. The research results show that the challenges for auditors in the Society 5.0 era include intense competition with artificial intelligence, which can replace audit functions. Therefore, auditor competency standards need to be enhanced in terms of mastering these technological systems to ensure effective control. Recommendations for future research could involve different methods and specify certain types of audits.